DISTRIBUSI SPASIAL DAN TEMPORAL FITOPLANKTON DI PERAIRAN LAUT TROPIS - Samria Abubakar; Nebuchadnezzar Akbar; Abdurrachman Baksir; Halikuddin Umasangadji; N Najamuddin; Irmalita Tahir; Rustam E Paembonan; Firdaut Ismail (Jurnal Kelautan, 2021)
ABSTRACTPhytoplankton are aquatic organisms that are free to float following the movement of the current. The distribution of phytoplankton is widespread throughout the body of water, both in rivers, estuaries, lakes, reservoirs, beaches and oceans. Water quality conditions will affect the presence of phytoplankton in certain waters. The purpose of this review article is to examine the types of phytoplankton that are spatially and temporally distributed and the physicochemical factors that affect the spatial and temporal distribution of phytoplankton in tropical waters. Assessing the spatial and temporal distribution of phytoplankton in tropical waters sourced from the latest national and international scientific journals and as a reference source of information for further research. The study in this paper is a literature review or literature study originating from the latest national and international scientific journals, with a focus on studying several research results that are relevant to the research topic, the study material is adjusted to the research data. The study area (tropical and subtropical) includes Indonesia, Malaysia, China, Brazil and India. The Bacillariophyceae class is found in all waters both spatially and temporally. The distribution of phytoplankton is spatially influenced by the presence of nutrients, then temporally the highest is found in the dry season. The distribution of phytoplankton is influenced by physical and chemical parameters of the waters (dissolved oxygen, temperature, salinity, pH, suspended solids/SPM, nitrate and phosphate) especially the presence of nutrients. Keywords: Phytoplankton, Distribution, Spatial and Temporal, Tropical WatersABSTRAKFitoplankton merupakan organisme akuatik yang bebas melayang mengikuti pergerakkan arah arus. Distribusi fitoplankton tersebar luas di seluruh badan perairan baik di sungai, muara, danau, waduk, pantai maupun samudera. Kondisi kualitas perairan akan mempengaruhi keberadaan fitoplankton di perairan tertentu. Tujuan review artikel ini mengkaji jenis fitoplankton yang terdistriusi secara spasial dan temporal serta faktor-faktor fisika kimia yang mempengaruhi distribusi spasial dan temporal fitoplankton di perairan tropis. Mengkaji distribusi spasial dan temporal fitoplankton di perairan tropis yang bersumber dari berbagai jurnal terbaru ilmiah nasional dan internasional serta sebagai sumber rujukan informasi untuk penelitian selanjutnya. Kajian pada tulisan ini merupakan telaah literatur atau studi pustaka yang berasal dari berbagai jurnal ilmiah terbaru nasional dan internasional, dengan fokus kajian beberapa hasil penelitian yang relevan dengan topik penelitian, materi kajian disesuaikan dengan data penelitian. Wilayah lokasi penelitian (tropis dan subtropis) meliputi Indonesia, Malaysia, Cina, Brazil dan India.Kelas Bacillariophyceae ditemukan di seluruh perairan baik secara spasial dan temporal. Distribusi fitoplankton secara spasial di pengaruhi keberadaan nutrien, kemudian secara temporal tertinggi ditemukan pada musim kemarau. Distribusi fitoplankton dipengaruhi parameter fisika dan kimia perairan (Oksigen terlarut, suhu, salinitas, ph, padatan tersuspensi/SPM, nitrat dan fosfat) tertutama keberadaan unsur hara.Kata kunci: Fitoplankton, Disitribusi, Spasial dan Temporal, Perairan Tropis